Modeling of outdoor natural ventilation and energy performance for buildings in an industrial park - Tan, Joel Heang Kuan. (2013)
In tropical countries such as Singapore, roof temperatures can get very hot during the day. In order to cool the building to comfortable temperatures, fans and air conditioning are used and they take up considerable amount of electricity.